Revit: Optimize Your BIM Workflow. - Bryant, Shaun (linkedin.com, 2020)
Learn the fundamentals of the BIM philosophy, how it fits into industry usage and government strategies, and how to use Revit to optimize CAD workflows that relate to BIM.